PERAN TERAPI AKUPUNKTUR PADA CARPAL TUNNEL SYNDROME - Wahyuningsih Djaali; Christina Lanny Simadibrata; Irma Nareswari; Dwi Rachma Helianthi; Kemas Abdurrohim (PERDOSNI, 2019)
ROLE OF ACUPUNCTURE THERAPY IN CARPAL TUNNEL SYNDROMEABSTRACTCarpal tunnel syndrome (CTS) is the most common peripheral neuropathy. In establishing a diagnosis of CTS, it requires several examinations that cannot stand alone. Symptoms from the anamnesis and signs of physical examination, such as Tinel test, Phalen test, press provocation examination, hand elevation examination and motor examination are needed. Nerve conduction velocity (NCV) investigation is also needed to diagnose CTS. Nevertheless, the clinical diagnosis of CTS can be done based on symptom history and physical examination using criteria by Rempel. Acupuncture is a modali- ty of non-pharmacological therapy performed by using fine needles at the acupuncture points. Acupuncture can improve the clinical symptoms of CTS patients through a mechanism of activation of the area in the brain that plays a role in sensory perception, through anti-inflammatory and anti-nociceptive mechanisms, and through mechanisms of protective effects on neural networks, thus providing therapeutic effects on neurological disorders due to CTS. By looking at the acupuncture mechanism, acupuncture can be a therapeutic choice for CTS to avoid the long-term side effects of medical therapy.Keywords: Acupuncture, carpal tunnel syndromeABSTRAKCarpal tunnel syndrome (CTS) merupakan neuropati perifer yang paling umum terjadi. Dalam menegakkan diagnosis CTS dibutuhkan beberapa pemeriksaan yang tidak dapat berdiri sendiri. Dibutuhkan gejala dari anamnesis, tanda dari pemeriksaan fisik, yaitu tes Tinel, tes Phalen, pemeriksaan provokasi tekan, pemeriksaan elevasi tangan dan pemeriksaan motorik. Juga dibutuhkan pemeriksaan penunjang kecepatan hantan saraf (KHS) untuk mendiagnosis pasti CTS. Sedangkan diagnosis klinis CTS dapat dilakukan berdasarkan anamnesis gejala dan pemeriksaan fisik dengan menggunakan kriteria oleh Rempel. Akupunktur merupakan modalitas terapi non-farmakologis yang dilakukan dengan penjaruman menggunakan jarum halus pada titik akupunktur. Akupunktur dapat memperbaiki gejala klinis pasien CTS melalui mekanisme aktivasi area di otak yang berperan pada persepsi sensorik, melalui mekanisme anti-inflamasi dan anti- nosiseptif, dan melalui mekanisme efek protektif pada jaringan saraf, sehingga memberikan efek terapeutik pada kelainan neurologis akibat CTS. Dengan melihat mekanisme akupunktur tersebut maka akupunktur dapat menjadi pilihan terapi pada CTS untuk menghindari efek samping jangka panjang dari terapi medikamentosa.Kata kunci: Akupunktur, carpal tunnel syndrome